Mucous extravasation phenomena in babies - Luciana Monti Lima; Rosana de Fátima Possobon; Fábio Ramôa Pires; Antonio Bento Alves de Moraes (Universidade Estadual de Campinas, 2015)
Mucous extravasation phenomena are rare in children in the first year of age. The authors report a case of a mucocele in the lower lip of an 8-month-old child and a case of congenital ranula. The patients didn't receive any treatment for the lesions and are under clinical follow-up for 14 months with signs of spontaneous remission of both lesions. Treatment indications and difficulties in the management of patients in this age group are discussed.